Karakteristik Tanaman Hias Pekarangan Rumah di Kelurahan Plaju Ulu Kota Palembang - Pebriana Kartika Sari; Dewi Rosanti; Yunita Panca Putri (Indobiosains, 2022)
ABSTRACT Research on the morphological characteristics of ornamental plant species in the home garden in Plaju Ulu Village, Palembang City, has been carried out from March to June 2021, aiming to determine the morphological characteristics of ornamental plants in Plaju Ulu Village, Palembang City. This study uses a descriptive survey method by exploring the village area as many as 3 RT. Observations were made by looking directly at the ornamental plants found and then recorded, photographed and then described morphologically. The results obtained 2 classes, 21 orders, 24 families, 36 genera and 36 species of ornamental plants. The species obtained had roots (Radix) with a fibrous root system (Radix adventicia) and tap (Radix primaria). The stem has a wet stem structure and woody shrubs and pseudo stems that are modified into rhizomes. Leaves are heart-shaped, shield, oblong, sword, lanceolate, elongated, triangular, ovoid, round and asymmetrical. Flowers have a single flower structure and compound flowers, cobs, bunches, umbrellas, grains, pots and cups. The fruit structure is a single true fruit dry, box fruit, buni fruit, bracket fruit, kendaga fruit and fleshy pseudo fruit. Accessory organs consist of tubers and spines. Keywords: Ornamental plants, Morphological characteristics.